From Social Funds to Local Governance and Social Inclusion Programs : A Prospective Review From the ECA Region - Technical Annexes - World Bank (2012)
The role and relevance of Social Fund Community-Driven Development (SF/CDD) has been highly debated in the international development community. Some conceive these programs only as parallel and temporary arrangements that can ensure short-term delivery of development benefits. Others emphasize the flexibility of the SF/CDD instrument in adopting different institutional forms depending on the country context, and their contributions to long-term development challenges. The aim of this study is to provide guidance on the question of social fund relevance. The report is organized into six chapters and a set of annexes. Chapter 1 defines social funds and their main rationales. Chapter 2 provides an overview of their origins in ECA, basic facts about the Bank operations and SF performance, and develops a typology based on policy objectives. Chapter 3 summarizes the institutional arrangements of social funds in the Region and then reviews them within the wider vision of optimal public sector arrangements. Chapter 4 looks at local infrastructure and governance funds, evaluating their design against a set of good practice benchmarks for promoting local governance, and drawing implications for the future. Chapter 5 conducts a similar exercise but for social inclusion funds. The final chapter summarizes the main answers to the study questions and elaborates a set of options for future engagement with social funds, taking into account different country contexts. In the Second Volume, Annexes provide more detailed background material.